Meta Analysis: Effects of Prelacteal Feeding and Vitamin A Supplementary Intake on Stunting in Children Aged 6-59 Months - Alifariani, Aulia; Murti, Bhisma; Adriani, Rita Benya (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Stunting describes the condition of failure to thrive in children under five years old (toddlers) due to chronic malnutrition and recurrent infections, especially in the first 1,000 days of life as a golden period with proper nutrition. This study aimed to examine the effect of prelacteal feeding and vitamin A on the incidence of stunting in children aged 6-59 months using a meta-analysis. Subjects and Method: The meta-analysis was carried out using the PRISMA flowchart and the PICO model. Population: children aged 6-59 months. Intervention: giving prelacteal feeding and vitamin A. Comparison: not giving prelacteal feeding and vitamin A. Outcome: stunting. The online databases used are Google Scholar, ProQuest and Elsevier with the keywords “Stunting” AND “Prelacteal feeding” AND “Vitamin A” AND “Children Aged 6–59 Months” AND “Multivariate” AND “Cross Sectional”. There were 15 cross-sectional studies published in 2013-2023 that met the inclusion criteria. Analysis was performed with RevMan 5.3. Results: A meta-analysis of 15 articles with a cross-sectional study design from different countries, namely Ethiopia, Uganda, Somalia, Indonesia and Sudan in children aged 6-59 months with a total sample of 94,212 research subjects. The results of the meta-analysis showed that there was an effect of not being given prelacteal feeding on the reduced risk of stunting in children aged 6-59 months. Children who were not given prelacteal feeding had 0.57 times the risk of stunting compared to those who were given prelacteal feeding (aOR= 0.57; 95% CI= 0.38 to 0.84; p= 0.005), Children who were not given vitamin A had a risk of being stunted 1.19 times compared to children who were given vitamin A (aOR= 1.19; 95% CI= 1.00 to 1.41; p= 0.050). Conclusion: Children who are not given prelacteal feeding and children who are given vitamin A reduce the risk of stunting in children aged 6-59 months. Keywords: prelacteal feeding, vitamin A, stunting, children aged 6-59 months. Correspondence:Aulia Alifariani. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: aulia.alifariani26@gmail.com. Mobile: +6282236887887.